GEOLOGICAL AND PETROLOGICAL CHARACTERS OF THE PLUTONIC ROCKS IN THE LUNCKERYGGEN-BRATTNIPENE REGION, SØR RONDANE MOUNTAINS, EAST ANTARCTICA - サキヤマ, トオル; タカハシ, ユウヘイ; オサナイ, ヤスヒト; SAKIYAMA, Tohru; TAKAHASHI, Yuhei; OSANAI, Yasuhito (National Institute of Polar Research, 1988)
P(論文) Plutonic rocks in the Lunckeryggen-Brattnipene region, Sør Rondane Mountains are divided into the older (late Proterozoic) and younger (early Paleozoic) intrusive rocks. The older intrusive rocks are composed of tonalite, quartz diorite, granodiorite and small sheet-like granite, granodiorite and trondhjemite. They have a gneissose structure and show a concordant relation to the surrounding metamorphic rocks. On the basis of their field occurrences, it seems that they have intruded before or during the period of the regional mylonitization. The younger intrusive rocks are composed of syenite, quartz syenite and granite. They occur as stocks or dikes intruding discordantly into the surrounding rocks. The older intrusive rocks give low values of magnetic susceptibility in general, while most of the younger intrusive rocks give high magnetic values in Lunckeryggen and the neighborhood. Magnetic values on the discordant granites of the younger stage decrease northward in the Lunckeryggen-Brattnipene region. Moreover, the magnetic values of the younger intrusive rocks in the western Sør Rondane Mountains show a possibility that the lateral variation extends farther west from the Lunckeryggen-Brattnipene region. The younger intrusive rocks are composed of alkaline rocks in contrast with the older intrusive rocks dominated by tonalite and granodiorite with low K_2O content in the Sør Rondane Mountains. Syenitic rocks in the Sør Rondane Mountains are characterized by high K_2O and low Na_2O contents. Such extremely high K_2O/Na_2O ratios correspond to that of the syenitic rocks in the Yamato and Belgica Mountains and it is considered that the high K_2O/Na_2O ratio may be a general characteristic of the early Paleozoic plutonism in the eastern Queen Maud Land. The transition of the plutonism from calc-alkaline to alkaline affinity corresponds to the tendency of the Pan-African magmatism. departmental bulletin paper